Efektivitas Pengelolaan Madrasah Ibtidaiyah terhadap Pengaruh Adversity Quotient, Time Management, dan Communication Management Kepala Madrasah - Muhamad Suhardi; Zinnurain Zinnurain; Rusi Rusmiati Aliyyah (Alignment:Journal of Administration and Educational Management, 2021)
The purpose of the study was to find the effect of adversity quotient, time management, and communication management of madrasah principals on the effectiveness of the management of Madrasah Ibtidaiyah (MI) in Lombok, West Nusa Tenggara for the academic year 2020/2021. This research method is quantitative with the sampling method in the form of a survey. Data analysis was carried out using path analysis techniques. The results showed that 1) adversity quotient, time management, and communication management of the madrasah principal had a direct positive effect on the effectiveness of madrasah ibtidaiyah management; 2) the adversity quotient has a direct positive effect on the time management and communication management of the head of Madrasah Ibtidaiyah. In conclusion, there is an effect of Adversity Quotient, Time Management, and Communication Management of Madrasah Principals on the Effectiveness of Management of Islamic Madrasahs in Lombok, West Nusa Tenggara Province for the 2020/2021 Academic Year. Keywords: Adversity Quotient, Communication Management, Head of Madrasah, Time Management